Shaping Speaking Skills Through Role-Play: Classroom Dynamics In Workplace Training - Sukmalasari, Ristha; Fadilla Oktaviana; Yayu Heryatun (Universitas Sulawesi Barat, 2026)
The demands of spontaneous and confident communication are still major challenges for adult learners in professional settings. However, role-play is often used in speaking classes that are carried out in academic contexts with homogeneous participants or in certain educational settings. However, there are still limited studies that examine how role-play functions in heterogeneous workplacetrainin contexts involving participants with diverse professional roles,ages, and English proficiency levels. This study aims to explore how classroom dynamics through role-play activities shape speaking skills in workplace English training. A qualitative approach was employed involving fifteen employees at PT Pulp Indonesia from different professional divisions who participated in a ten-session English training program. Data were collected through classroom observation during four role-play sessions and semi-structured interviews, then analyzed through thematic analysis following Braun and Clarke’s framework. The findings indicate that the speaking development did not occur instantly through task repetition, but emerged through a gradual transformation of classroom dynamics. In the early stages, there is an unequal interaction of participants, dominated by certain participants, anxiety, and lack of confidence, especially in older participants or those with low levels of English proficiency. As the role-play session progresses, emotional tension decreases and interaction patterns become cooperative. Passive participants initiate and show a more spontaneous response. These findings show that the development of speaking skills is formed through the reconstruction of participation patterns and the reduction of psychological barriers in the context of heterogeneous professional training. These findings contribute to the understanding of workplace English pedagogy by highlighting the role of social dynamics and professional hierarchies in shaping participation and the development of speaking skills in the context of training.